Driving regional economy: Digital technology adoption's role for effective distribution of islamic social finance in Indonesia - Munifatussaidah, Asma; Zahara, Jihan Nabila; Resiana, Rani Surya; Ningsih, Lita Ayudha (Jurnal Ekonomi & Studi Pembangunan, 2024)
Indonesia holds significant potential in leveraging the vast collection of Islamic social funds. Amid the widespread digital transformation within financial institutions, it is critical to examine the impact of the adoption of digital technology in affecting the distribution of Islamic social finance and its subsequent impact on regional economic development in Indonesia. The research utilized data from 21 provinces in Indonesia to construct a regression model that investigates and evaluates the performance of Islamic social fund distribution concerning regional economic growth. This study integrates a moderation effect model to assess the impact of digital adoption on this relationship. Grouped regression models were used to investigate further regional variations, with robustness checks conducted across different fundraising levels. The findings reveal a significant influence of Islamic social fund distribution on regional economic development, with digital adoption—measured by access to and use of digital technology—acting as a considerable moderator. Further heterogeneity analysis reveals that provinces with lower GINI coefficients experience a more pronounced dampening effect of Islamic social fund distribution on regional economic development, moderated by the extent of digital adoption. This research offers new insights into the relationships between Islamic social fund distribution and digital adoption (ICT) in regional economic development, providing strategic implications for philanthropic institutions and policymakers considering Islamic social fund management.